PERLAKUAN MEKANIS DAN PEMBERIAN ETILEN DALAM MENGINDUKSI PEMBENTUKAN TERPENOID PADA POHON GAHARU (Aquilaria beccariana) - Rawana (Fakultas Kehutanan Institut Pertanian STIPER Yogyakarta, 2012)
The parameters of color change zone and color darkness level are affected by the treatment of screw deepthness. The parameter of fragrant level is also affected by treatment of screw deepthness. The treatment of screw deepthness (1,54 cm) is the best, then screw deepthness 1,27 cm and screw deepthness 1 cm respectively. The parameter of terpenoid content is significantly affected by interaction of treatment screw deepthness and giving etepon. Treatment combination of etepon concentration 1,.5% and screw deepthness 1 cm is the best to give terpenoid content value (1,266). Keywords : Mechanical treatment, Etilen, Terpenoid